OPTIMALISASI INVESTASI PENDIDIKAN MELALUI PERSPEKTIF ANALISIS BIAYA DAN MANFAAT (ABM) - Sahrul Adi Amanatulloh; Yustina Trihartatik; Matius Kurniawan; Nurkolis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education investment is a strategic step to improve the quality of human resources and economic growth. This study uses library research with a cost-benefit analysis (ABM) approach to evaluate the effectiveness of education investment in Indonesia, including direct costs, indirect costs, and benefits such as increased income up to 2.5 times and positive social impacts, such as reduced inequality. The results show a favorable cost-benefit ratio, especially in higher education. Recommendations include increasing the budget, expanding scholarships, and integrating technology to optimize education investment.